Antitick potential and chemical variability among Ageratum conyzoides L. germplasms collected from Eastern and Western Ghats of India. Issue 8 (17th November 2019) - Kumar, Bhanu; Misra, Ankita; Kumar, Sachin; Rawat, Ajay Kumar Singh; Rawat, Yashwant Singh; Ghosh, Srikant; Srivastava, Sharad
ABSTRACT: Ageratum conyzoides L. is a common weed in many tropical and subtropical countries including India. The present study aimed to evaluate the antitick potential using Adult Immersion Test (AIT) and variability of its phytoconstituents with the developed HPTLC method in germplasms collected from Eastern and Western Ghats of India. Percent tick mortality at 8% concentration ranged from 10.0 ± 0.2 to 85.0 ± 2.9. Precocene I content ranged from 0.0004% to 0.072%, Precocene II content varied from 0.001% to 0.035%, and Caryophyllene oxide content was found to range from 0.0001% to 0.0023% in crude drug. Precocene II was positively correlated (coefficient = 0.656) with tick mortality (%) in the germplasm collected from Western Ghats. However, in Eastern Ghat samples, Precocene I was positively correlated (coefficient = 0.550) with per cent tick mortality. There is significant variation in marker compound content as well as antitick activity of the extracts; however, a direct correlation among marker compounds and antitick activity was not observed. This indicates there may be some other phytomolecules responsible for antitick activity of the extract. This study will lead to a potential source of quality raw material for the industry in developing herbal acaricide.